Analysis Of Promotion And Service Quality On Savings Decisions At Pt Bank Sumut Tcp Market Tavip Mediated Saving Intention - Suci Indah Hakiki; Elfitra Desy Surya; Nurafrina Siregar (Yayasan Multidimensi Kreatif, 2025)
This study aims to test and analyze the influence of PROMOTION and service quality on savings decisions at PT Bank Sumut KCP Pasar Tavip mediated by saving intentions. The method used in this study is a quantitative method. Data analysis techniques using SMART PLS. Data collection techniques using Quesioner and interviews. The population in this study is 370 customers. By using the slovin formula, a sample of 190 customers was obtained. The results of the study show that promotion has a positive and significant effect on the decision to save at PT Bank Sumut KCP Pasar Tavip. Product quality has a positive and significant effect on the decision to save at PT Bank Sumut KCP Pasar Tavip. Promotion and service quality have a positive and significant effect on the decision to save PT Bank Sumut KCP Pasar Tavip which is mediated by the intention to save PT Bank Sumut KCP Pasar Tavip.